Comparison of BioFire FilmArray gastrointestinal panel versus Luminex xTAG Gastrointestinal Pathogen Panel (xTAG GPP) for diarrheal pathogen detection in China. (October 2020) - Zhan, Zhifei; Guo, Jiayin; Xiao, Yong; He, Zixiang; Xia, Xin; Huang, Zheng; Guan, Hongxia; Ling, Xia; Li, Jie; Diao, Baowei; Zhao, Hongqun; Kan, Biao; et al.
Highlights: The two panels were highly consistent in detecting norovirus, rotavirus and Campylobacter . Low concentration targets were more often detected by FilmArray than xTAG GPP. The xTAG GPP was more likely to be affected by amplification inhibitors. Several defects of xTAG GPP were found in detecting enterotoxigenic Escherichia coli. Abstract: Objectives: To compare the performance of two syndromic panels: Luminex xTAG Gastrointestinal Pathogen Panel (GPP) and FilmArray Gastrointestinal (GI) panel. Methods: A total of 243 diarrhea specimens were detected by two panels in parallel, and the inconsistent results were analyzed by real-time PCR or reverse transcription PCR (RT-PCR). The target concentration in specimens was examined by comparing the crossing point values of FilmArray, the median fluorescence intensity of xTAG and the cycle threshold values in any discrepancies. Results: For pathogens detected by both panels, the positive rates of FilmArray GI and xTAG GPP were 65.0% and 48.6%, respectively. The two panels showed high consistency (kappa ≥0.74) in detecting norovirus, rotavirus and Campylobacter, while there was low consistency (kappa ≤0.40) in detecting Cryptosporidium, Salmonella, Shiga toxin-producing Escherichia coli (STEC) and enterotoxigenic Escherichia coli (ETEC). Samples with low concentration targets were more often detected by FilmArray than with xTAG GPP. The xTAG GPP was more likely to be affected by amplification inhibitors. Several defects of xTAG GPP were found in detecting ETEC. Conclusions: FilmArray was more sensitive. For specimens with low target concentrations or containing ETEC heat stable enterotoxin, the false negatives of xTAG GPP need to be considered.